Pendampingan Dan Pelatihan Komunikasi Hubungan Pelanggan Untuk Menciptakan Loyalitas Wisatawan Desa Gada Kecamatan Gunungsitoli Barat Kota Gunungsitoli - Dian Septiana Sari (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2021)
The goal to be achieved from this service is to increase public understanding and knowledge in implementing Customer Relations Communication and Customer Loyalty. Then it is also hoped that the community will be able to optimize tourist visitors in Gada village. This service activity plan will be carried out for 2 days starting from field observations to counseling with the theme of efforts to improve understanding of Customer Relationship Communication and Customer Loyalty properly and correctly. The implementation method uses lectures, discussions and questions and answers. The result of this service is that after mentoring activities are carried out in the village community, the members understand and are able to implement Customer Relations and Customer Loyalty Communication in a Specific, measurable, achievable, realistic or reasonable manner, not a fantasy that cannot be realized and has a target time achievement. Service partners can also optimize customer communication techniques properly so as to create opportunities to increase tourist loyalty